Relationship between quality and utilisation of oral health service in Community Health Centers of Padang City - Darma, Azri; Oenzil, Fadil; Hidayati, Hidayati (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2018)
Introduction:Â Increasing incidence of oral diseases have not been balanced by the utilisation of oral health care units available, especially at the level of basic services such as Community Health Centers (Puskemas).Â This study was aimed to determine the relationship between the quality and the utilisation of health services in Community Health Centers of Padang City. Methods: This study was a survey research with cross-sectional design, Samples have been taken using a randomÂ sampling with total samples of 131 respondents, and statistical analysis used was the chi square test. The independent variable was the service Â quality in terms of the patients satisfactionory dimensions, while the dependent variable was utilisation of the oral health services with categories of community health centers that were averagely visited < 9 times daily andÂ â¥ 9 times daily. Results: There was a significantÂ relationship (p-value < 0.05) between several satisfaction dimensions variables (a wide parking area; hygienic park; assessment of dental health that always performed by the dentists; a friendly services by the counter clerks; and the dentists willingness to listen to the patients complaints), and the utilisation of the oral health service in Community Health Centers of Padang City. Conclusion:Â Most patients are satisfied with the quality of oral health serviceÂ in Community Health Centers of Padang City. The visitation and utilisation rate of the patients, however, are not affected significantly by most of their satisfactory dimensions, except for five dimensions which were, wide parking area,Â garbage-free parking area, assessment of dental health that always performed by the dentists, a friendly services by the counter clerks, and the dentists willingness to listen to the patients complaints.